2002
DOI: 10.1080/000164802753648295
|View full text |Cite
|
Sign up to set email alerts
|

Swelling of the Intratemporal Facial Nerve in Ramsay Hunt Syndrome

Abstract: Although Ramsay Hunt syndrome is one of the most important diseases causing peripheral facial palsy, the detailed pathology of the disease in the intratemporal facial nerve remains unclear. The purpose of this study was to increase knowledge of the pathogenesis of the syndrome by means of surgical findings. Between April 1976 and March 1997 we performed subtotal decompression of the facial nerve in 74 patients with severe Ramsay Hunt syndrome. The grade of nerve swelling was assessed using a microscope and rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
1

Year Published

2004
2004
2022
2022

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(9 citation statements)
references
References 22 publications
0
8
1
Order By: Relevance
“…The massive bulbous swelling of the meatal segment of the facial nerve occurring in cases of severe Bell's palsy is a typical demonstration of engorgement of axonal flow. Next, the second narrowest site of the facial canal at the stapes may also strangulate the facial nerve when inflammatory edema on the geniculate ganglion spreads to the peripheral site of the geniculate ganglion, because swelling of the horizontal segment including the geniculate ganglion is observed in the decompressed facial nerve, compared with the pyramidal and vertical segments [17,18].…”
Section: Discussionmentioning
confidence: 99%
“…The massive bulbous swelling of the meatal segment of the facial nerve occurring in cases of severe Bell's palsy is a typical demonstration of engorgement of axonal flow. Next, the second narrowest site of the facial canal at the stapes may also strangulate the facial nerve when inflammatory edema on the geniculate ganglion spreads to the peripheral site of the geniculate ganglion, because swelling of the horizontal segment including the geniculate ganglion is observed in the decompressed facial nerve, compared with the pyramidal and vertical segments [17,18].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, MRI examinations have revealed abnormalities localized not only to the inner ear and vestibulocochlear nerve, but also to the facial nerve (Brandle et al, 1996;Chung et al, 2015). The intratemporal facial nerve including the geniculate ganglion seems to swell in the acute phase of RHS, which has been observed during subtotal decompression surgery (Honda et al, 2002). Moreover, presence of VZV DNA has been found in the facial nerve sheath and middle ear mucosa as well as vesicles and CSF (Murakami et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…Yanagihara et al observed changes in the facial nerve in Bell's palsy and Ramsay Hunt syndrome patients over time 15,16. They reported that facial nerve edema lasted longer and was more severe in Ramsay Hunt syndrome than in Bell's palsy, but in all patients, the edema proceeded from the geniculate ganglion towards the peripheral area as time progressed and the facial nerve edema decreased.…”
Section: Discussionmentioning
confidence: 99%